The Implementation of an E-Module to Improve Students’ Knowledge and Learning Achievement in the Elements of Refrigeration Instalation Systems - Wardani, Aditya; Khumaedi, Muhammad; Sutopo, Yeri (Universitas Negeri Semarang, 2025)
The availability of innovative, interactive, and student-centered learning media to facilitate the understanding of marketing techniques, air conditioning, and cooling systems, particularly the components of refrigeration installation systems, remains insufficient. It happened since interactive and contextual learning media at school were limited. This study aimed to develop and apply an E-module as an effective learning medium to improve students’ learning achievement in the element of refrigeration installation. The presented research adopted the ADDIE, which comprises five steps: analysis, design, development, implementation, and evaluation. The subjects of this study were XI-grade students from two different vocational schools in Central Java. The participants were divided into an experimental group (utilizing an E-Module) and a control group (receiving conventional instruction). The instruments employed included expert validation sheets, practicality questionnaires, and learning outcome tests. The data showed that the E-module was very feasible, with a practical score gained 94% and the N-Gain of the experiment class achieved 0.74 (high level category). Furthermore, the t-test showed a difference between the experimental and control classes. In conclusion, E-module was declared very feasible, practical, and effective enough to be used in vocation learning, especially on improving students’ knowledge in refrigerator installation system of cooling technique and air conditioning system such as sytem component of instalation refigerator, conceptual knowledge (understanding colling and workflow sytem), and procedural knowledge (explaining the steps for installing and maintaining the refrigeration system).